2018
DOI: 10.1002/ccd.27540
|View full text |Cite
|
Sign up to set email alerts
|

The five key “ingredients” for improving outcomes in cardiogenic shock complicating acute myocardial infarction

Abstract: Cardiogenic shock in the setting of acute myocardial infarction (AMICS) carries high mortality. A systematic, protocol-driven, approach to AMICS may improve outcomes. The 5 key "ingredients" for the managements of AMICS are: (a) early diagnosis; (b) hemodynamic assessment; (c) culprit-only coronary revascularization; (d) judicious use of mechanic circulatory support; (e) expert in-hospital treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…A recent study showed that left ventricular remodeling (LVR) was observed in more than 30% of patients one year after AMI, and that LVR was strongly associated with hospitalization for HF [ All these aspects have to be included in the therapeutic panel of CS, overcoming the simplistic target of short-term survival. This ambitious objective can be achieved through the deployment of a multifaceted approach that includes myocardial reperfusion, hemodynamics stabilization, reduction of mechanical circulatory support (MCS)-associated complications, ventricular unloading, and control of local and systemic inflammation to limit infarct size and prevent LVR [16,17].…”
Section: The "Good Outcome" Of Cardiogenic Shock After Amimentioning
confidence: 99%
“…A recent study showed that left ventricular remodeling (LVR) was observed in more than 30% of patients one year after AMI, and that LVR was strongly associated with hospitalization for HF [ All these aspects have to be included in the therapeutic panel of CS, overcoming the simplistic target of short-term survival. This ambitious objective can be achieved through the deployment of a multifaceted approach that includes myocardial reperfusion, hemodynamics stabilization, reduction of mechanical circulatory support (MCS)-associated complications, ventricular unloading, and control of local and systemic inflammation to limit infarct size and prevent LVR [16,17].…”
Section: The "Good Outcome" Of Cardiogenic Shock After Amimentioning
confidence: 99%
“…In order to explore the concrete impact of rehabilitation exercise on non-cardiac myocardial injury, a scientific and reasonable rehabilitation exercise program was developed to promote the continuous improvement of its overall therapeutic effect [6] . The author first illustrated the application of optical microscope, and then from the specific reflection of non cardiac myocardial damage and formation mechanism are introduced, based on the cases were retrospectively analyzed experiment, to explore the rehabilitation exercise in the cardiac effects of myocardial injury treatment, and on the basis of this puts forward the corresponding scientific rehabilitation exercise plan [7] .…”
Section: Introductionmentioning
confidence: 99%